Postulat neutralności opodatkowania transgranicznych dochodów kapitałowych z perspektywy prawa europejskiego - Bacia, Bartosz (Kwartalnik Prawa Podatkowego, 2016)
This paper presents analysis of tax neutrality concepts such as capital export neutrality, capital import neutrality, capital ownership neutrality, and market neutrality as tools of international tax policy in the context of the EU law. Based on the body of the ECJ case law the paper examines whether the requirement of neutral taxation of cross-border capital income within the EU can be inferred from the relevant provisions of the Treaty providing for fundamental freedoms as well as the principle of non-discrimination. The requirement of neutral taxation of cross-border capital income can be met as side-effect of the full realization of the concept of internal market. However, there is insufficient legal basis to support the claim that the concept itself is embedded in the Treaty. Furthermore, it is argued that efficient mechanism of double taxation avoidance of cross-border income is a pre-condition of tax neutrality within the EU. In the light of the fundamental freedoms under EU law the exemption method allows for compliance with the Treaty, whereas the tax credit method proved under certain circumstances to adversely influence investment decisions of taxpayers. The paper criticizes the emerging trend in the ECJ’s jurisprudence which lead to disadvantageous treatment of cross-border situations. As thorough scrutiny of fundamental tax policies and ECJ case law reveals, justification for such approach can neither be derived from the territoriality of taxation principle as such nor from the well established concept of a “balanced allocation of taxing powers”.